Control of Cutaneous Leishmaniasis Using Deltamethrin Treated Nets in Comparison to Indoors Residual Spraying in a Rural Area of Iran - Mohammad Hassan KAYEDI; Yavar RASSI; Ali CHEGENI-SHARAFI; Reza ROSTAMI; Sayena RAFIZADEH; Nargess ABDALI (Tehran University of Medical Sciences, 2017)
Background: Cutaneous leishmaniasis (CL) is an important vector-borne disease in Iran. The present study aimed to evaluate the efficacy of Deltamethrin treated nets in comparison to Indoors Residual Spraying (IRS) for the control of leishmaniasis in a new focal area of Iran. Methods: The study was carried out in 5 villages in the west of Iran during 2012-2013. One village was selected to the application of Insecticide Treated Nets (ITNs, 25 mg/m2 deltamethrin) among residents. Four other villages were considered for IRS using deltamethrin emulsion, 2.5% EG and Aicon 10WP. Spraying was repeated after 3 month. Other control methods e.g. environmental managements, and treatment of positive cases were carried out in all villages. Results: After 1 yr of trial, the cases of disease reduced from 50 to 2 and 128 to 5 for ITNs distributed nets and use of IRS in the villages, respectively. Conclusion: Reduction of CL cases in both methods were significant (P<0.001).